Maltrato infantil y rasgos de personalidad como predictores de agresividad en adolescentes - dos Santos Lopes Apolinário, Juliana (2024)
The present study aimed to verify whether personality traits, child abuse, and school environment influence aggressiveness. 245 male high school students from six public schools participated in the study. The Aggression Tendency Scale, the Big Five Personality Inventory, the Childhood Trauma Questionnaire, and a socioeconomic questionnaire administered collectively. Low-performing schools showed higher levels of physical and verbal aggres-sion than high-performing schools but no antisocial behavior. Regression analyses indicated that Agreeableness and low-performing schools were predictors of verbal [F(4,225) = 13.46, p < .001, R2 = .19] and physical aggression [F(3,231) = 18.10, p < .001, R2 = .19]. Agreeableness was a predictor of antisocial behavior [F (2,232) = 20.64, p < .001, R2 = .15]. Child abuse did not predict aggression.